2021
DOI: 10.5194/se-12-1051-2021
|View full text |Cite
|
Sign up to set email alerts
|

Transversely isotropic lower crust of Variscan central Europe imaged by ambient noise tomography of the Bohemian Massif

Abstract: Abstract. The recent development of ambient noise tomography, in combination with the increasing number of permanent seismic stations and dense networks of temporary stations operated during passive seismic experiments, provides a unique opportunity to build the first high-resolution 3-D shear wave velocity (vS) model of the entire crust of the Bohemian Massif (BM). This paper provides a regional-scale model of velocity distribution in the BM crust. The velocity model with a cell size of 22 km is built using a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 76 publications
1
13
1
Order By: Relevance
“…For a comparison with the picked data, we calculate the theoretical dispersion curves of these 1D velocity models (Figures 13C,D; Supplementary Figure S7C, Supplementary Figure S7D), the results of which clearly demonstrate an unsatisfactory match between the theoretical dispersion curves of these models and the F-J spectrograms (especially at the higher modes). Specifically, the theoretical dispersion curves corresponding to the 1D models under the four arrays extracted from the models of Lu et al (2018) and Kvapil et al (2021) are overall lower than picked data; the two 1D models using the phase velocity dispersion curves for the inversion (Kästle et al, 2018;Růžek et al, 2016), especially the models from Kästle et al (2018) present better fitting results for fundamental mode, but large deviations at the higher modes are still observed for the two models. Our models obtained via the joint inversion of the multimodal dispersion curves match well with the fundamental mode and higher modes for the four arrays.…”
Section: Crustal S-wave Velocity Models In the Northwestern Bohemian ...mentioning
confidence: 90%
See 4 more Smart Citations
“…For a comparison with the picked data, we calculate the theoretical dispersion curves of these 1D velocity models (Figures 13C,D; Supplementary Figure S7C, Supplementary Figure S7D), the results of which clearly demonstrate an unsatisfactory match between the theoretical dispersion curves of these models and the F-J spectrograms (especially at the higher modes). Specifically, the theoretical dispersion curves corresponding to the 1D models under the four arrays extracted from the models of Lu et al (2018) and Kvapil et al (2021) are overall lower than picked data; the two 1D models using the phase velocity dispersion curves for the inversion (Kästle et al, 2018;Růžek et al, 2016), especially the models from Kästle et al (2018) present better fitting results for fundamental mode, but large deviations at the higher modes are still observed for the two models. Our models obtained via the joint inversion of the multimodal dispersion curves match well with the fundamental mode and higher modes for the four arrays.…”
Section: Crustal S-wave Velocity Models In the Northwestern Bohemian ...mentioning
confidence: 90%
“…In comparison, the S-wave velocities in our models are higher than those in the other models at depths of ~30-40 km. In addition, the S-wave velocities in the models from Kvapil et al (2021) are obviously lower than those in other models (shown in Figure 13, Supplementary Figure S7 and Supplementary Figure S8), even the models of Lu et al (2018), who also used group velocity dispersion curves for inversion. The general group velocity level of the dispersion curves in Kvapil et al (2021) is lower than the level presented in Lu et al (2018), which may be the main reason for the models' discrepancy.…”
Section: Crustal S-wave Velocity Models In the Northwestern Bohemian ...mentioning
confidence: 97%
See 3 more Smart Citations